Dismal Science, Accounting and Newton’s Second Law : Identifying Force and Rigidity in Public Expenditure Analysis - Merotto, Dino; Hayati, Fayavar; Stephan, David; Bataille, William (World Bank, Washington, DC, 2015)
This paper proposes a new measure of public expenditure force that policy makers and budget analysts should track in detail over time in routine fiscal monitoring. The paper suggests that adopting the measure will not only warn policy makers of possible impending fiscal pressures, but will help them to differentiate between those budgetary pressures that are temporary and those that may require reforms. The main utility of the expenditure force measure will be in country fiscal analysis. Measuring force across the entire budget allows practitioners to monitor and decompose the micro drivers of public spending pressure, watch out for rapidly expanding spending lines, and identify priorities for reform before these pressures lead to macro fiscal problems. Yet by its construct, spending force is internationally comparable, and independent of expenditure levels or spending types. This could allow global monitoring comparisons and global research into the drivers of public spending force across particular types of country characteristics and economic conditions. In time, and as more data become available, researchers can use the force measure to compare and contrast the dynamics of expenditure types across countries. For example the measure can be used to explore what gives some spending types an initial impulse; whether underlying factors cause different public spending categories to grow faster than average, or to accelerate over time; and what successful countries have done to manage rising force without damaging public services. Since force seems to be a decent predictor of fiscal episodes, it is suggested that “speed limits” for spending might be a feasible component of fiscal rules.